Transient transformation of mammalian cells by MN protein, a tumor-associated cell adhesion molecule with carbonic anhydrase activity - Zavada, J; Zavadova, Z; Machon, O; Kutinova, L; Opavsky, R; Pastorek, J (International journal of oncology, 1997)
The MN protein is associated with certain human carcinomas, but absent in most normal tissues. It is a transmembrane protein; its extracellular part contains a domain homologous with carbonic anhydrases (CAs) and a proteoglycan-like region. In the present study, we observed that cells (human CGL1 and mouse NIH3T3 cells) transfected with MN cDNA showed morphologic transformation, but reverted to normal phenotype after 4-5 weeks. This reversion was not due to the loss, silencing, or mutations of MN insert. We also found that MN protein exerted CA enzymatic activity, but this was not relevant for morphologic transformation of cells. MN is an adhesion protein, involved in cell-to-cell contacts, this probably could explain its role in tumorigenesis.